Ethnobotany of the genus Physalis L. (Solanaceae) in the South American Gran Chaco - Arenas Rodriguez, Pastor (2013)
The species of the genus Physalis L. (Solanaceae) are grasses or shrubs, practically all of which are native to America. They are known for their application as foods and medicines in several different countries of the continent. The genus is represented in the Gran Chaco by 6 taxa, of which Physalis viscosa L. is the most widespread and of greatest local use. This paper presents ethnobotanical, floristic and ecological data recorded for the Physalis that live in the region. Likewise, bibliographical sources were examined for references to the genus in the Gran Chaco and other parts of America. During field work original data were recorded and the reference plant material was collected. The research study included nine indigenous groups as well as the rural population of the region. The vernacular names of the different species collected, their uses and forms of use are provided. These results are compared with the references from other human groups in America, and the role of these plants in the context of each culture is discussed.